Pelatihan desain Logo dan teknik Fotografi bagi pengusaha muda binaan YPSK Lampung untuk meningkatkan minat pembelian konsumen - Kusumawati, Theresia Dhian (Penerbit Goodwood, 2024)
Purpose: The contribution of this activity is that these young Entrepreneurs can be more creative in increasing product value. With creativity in the technique of making logos on packaging and photography products techniques, it is hoped that it will be able to increase consumer awareness and interest in buying these products so that they can increase sales. Methodology/approach: This community service activity is carried out through various stages, namely observations and interviews with target participants regarding the efforts that have been implemented and the obstacles faced as material or ideas for community service themes, then the service team offers solutions to the problems faced. Then the service team provided material related to making logos on packaging and photography techniques. Followed by the Coaching Clinic Method in the form of assistance in creating logos and product photography techniques. Results/findings: Based on the results of the logo work that has been created by the training participants, it can be seen that the participants have been able to master attractive packaging techniques by creating logos using color and typography. Also in terms of product photography techniques, participants have been able to master interesting product photography techniques, taking photos from good angles, good lighting techniques, and using supporting materials that support the quality of attractive product photography. Limitation: Through online marketing, the level of consumer awareness of these beverage products increases, thereby increasing sales levels. Contribution: The contribution of this activity is that after attending the training and coaching clinic, young Lampung entrepreneurs can be more creative in designing logos on packaging and making attractive photography so they can create attractive promotional designs through online marketing, namely WhatsApp, Instagram, and Facebook.